Electricity-Water Consumption and Metropolitan Economic Growth: An Empirical Dual Sectors Dynamic Equilibrium Model - He, Yiming; Gao, Shaoui (Frontiers in Energy Research, 2021)
This paper incorporates a time series data set from 1950 to 2014 in Guangzhou of China into a dual sectors dynamic equilibrium model. It presents a theoretical prediction on the interactions between electricity consumption, water consumption, and the metropolitan economic growth. Consistent with this prediction, electricity consumption and water consumption by themselves appear to have significant effects on metropolitan economic performance. The cointegration techniques show that electricity consumption, water consumption, and the metropolitan economic performance have long run equilibrium relationship. The results of kernel-based regularized least squares reveal that metropolitan economic growth is positively correlated with electricity consumption. Also consistent with theory, water consumption is positively associated with metropolitan economic performance. These results are generally stable and hold with alternative measures of unit roots, with alternative estimation strategies, and with or without controlling for trends, intercepts, and break points.